The impact of trade secrecy on COVID 19 vaccines: an analysis through a human flourishing lens - Sumanadasa, D. (Faculty of Law, University of Colombo, 2021)
The novel coronavirus disease is far from over causing enormous challenges to the human race. At the same time, COVID-19 vaccination tells us another story about the world dominance by big pharma companies through their intellectual property (IP) rights. Whereas many have known that vaccinations are protected under the patent regime, what is untold is that some aspects of vaccines have been protected as trade secrets. For instance, certain information including mRNA manufacturing technologies of Pfizer-BioNTech COVID-19 Vaccine has been kept as trade secrets. This paper argues that such protection may impede the human flourishing. As postulated by Amartya Sen and Martha Nussbaum, flourishing includes people's ability, functioning and freedom to achieve the capacities to live a dignified-full- fledged-life. Given the understanding that vaccination is the effective and sustainable way to overcome the problem, protecting vaccines and related aspects as trade secrets is highly problematic. First, protecting embryonic ideas, negative know-how and clinical trials data as trade secrets may contribute to slow-down the advanced medical solutions to the problem. Secondly, protecting related information as trade secrets may be having a chilling effect on follow-on innovation. Thirdly, when an invention is protected as a trade secret, it discourages manufacturers from successfully concluding voluntary licensing deals and technology transfers. This paper argues that these side effects of trade secrecy may impede central capabilities that a human should possess in order to live a complete and satisfying life with good health. Whereas there is a proposal from countries such as India and South Africa to temporarily waive IP rights over vaccines, it is yet to be implemented. Even if this proposal is implemented, such a measure will undoubtedly discourage investing in inventions on vaccines. As such, this research proposes to introduce a concept of‘compulsion in the public interest’ as an exception to trade secrets protection. Accordingly, when there is a global health crisis which challenges human existence and flourishing, a government should be able to force a trade secrets holder to reveal the secret in exchange for a royalty in order to reproduce the secret product or process. This proposal may be implemented in line with the compulsory licensing system of the patent regime.
Keywords: COVID-19 vaccine; intellectual property; trade secrets; human flourishing